Administraç\~ao e sustentabilidade da dívida pública no Brasil: Uma análise para o período 1995-2007 - Mário Jorge Mendonça; Manoel Carlos de Castro Pires; Luiz Alberto Medrano (Instituto de Pesquisa Econômica Aplicada (IPEA), 2008)
– This paper aims to evaluate how public debt management in Brazil has affected its sustainability in the 1996-2007 period. In 2003 Brazilian public debt management changed the trade off between cost minimization and risk minimization emphasizing the first element. Using a Markov-Switching model in order to model this policy change we access fiscal sustainability with Monte Carlo simulations. The results show that Brazilian public debt is sustainable in the medium run.
Keywords: C15; H63; H68; 330; Schuldenmanagement; Brasilien